Glyphosate resistance and EPSPS gene amplification confirmed in a waterhemp (Amaranthus tuberculatus) biotype from Connecticut - Jatinder S. Aulakh; Vipan Kumar; Nathaniel Westrick; Andrew J. Price; Amit J. Jhala (Agrosystems, Geosciences & Environment)
Abstract Waterhemp (Amaranthus tuberculatus) is an economically important broadleaf weed that threatens corn and soybean production across the United States. A waterhemp biotype (CT_Res [resistant biotype from Connecticut]) surviving multiple glyphosate applications was identified from a corn field in Connecticut (CT). Greenhouse and laboratory studies were conducted to (1) confirm glyphosate resistance in CT_Res waterhemp biotype and (2) investigate if the glyphosate resistance in CT_Res biotype is due to target‐site‐based mechanism. Dose‐response studies indicated that CT_Res biotype was 5.8‐fold more resistant to glyphosate compared to a known susceptible biotype (NE_Sus) from Nebraska. No point mutation was detected at Pro102 or Thr106 positions in the EPSPS gene of the CT_Res biotype. The quantitative polymerase chain reaction assays revealed that one of the three CT_Res waterhemp plants had 3.5‐fold higher EPSPS gene copy number (relative to the housekeeping CPS gene), whereas the other two plants did not reveal EPSPS gene amplification. Obviously, the EPSPS gene amplification partially explains glyphosate resistance in newly identified glyphosate‐resistant waterhemp biotype from CT, indicating that alternative mechanisms might exist. This research reports the first case of glyphosate resistance and EPSPS gene amplification in waterhemp from Connecticut and highlights the need for adoption of diversified weed control strategies to prevent its further spread.